Comparative vertical quality analysis using different methods for MBES data - Ferreira, Ítalo Oliveira; Coelho de Andrade, Laura; de Paula dos Santos, Afonso; de Oliveira, Júlio Cesar (The International Hydrographic Review, 2025)
Vertical quality evaluation in hydrographic surveys, particularly utilizing Multibeam Echosounders (MBES), presents challenges due to limited bathymetric information in obtaining homologous points and the absence of robust statistical criteria in depth estimation. This study addresses these challenges by proposing and validating the Point-to-Point (P2P) method, which prevents geostatistical interpolation while enhancing accuracy using a limited distance to search for the nearest neighbor and to find a probable homologous point. Three distinct methods were applied to compare depths of sounding lines and check line, namely Surface-to-Surface, Surface-to-Point, and Point-to-Point. The efficacy of the P2P method was established through a comprehensive evaluation of RMSE and ϕRobust, besides the discrepancies. This research underscores the significance of the P2P method, showcasing its superiority over conventional approaches and its potential to rectify the absence of statistical rigor in vertical quality assessment.